AFRICAN MEDICINAL PLANTS WITH ANTI-MYCOBACTERIUM TUBERCULOSIS ACTIVITY: A REVIEW - MAIKUDI USMAN, MOHAMMED; AISAMI, ABUBAKAR; MOHAMMED , SULAIMAN; SA’IDU , HARUNA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Tuberculosis (TB) is presently a major health pitfall as a result of Multidrug – resistant strains of bacilli. Reported estimate of 10·6 million people became ill with tuberculosis in 2021. Efforts are in progress to eradicate TB using new therapeutic drugs. This review is aimed at highlighting the work on anti-mycobacterium tuberculosis plants in Africa; it involves different plants and their chemical constituents exhibiting anti-mycobacterial properties. Some of the plant species identified and their chemical constituents include Plectranthus neochilus, Allium sativum Tamarindus indica andCymbopogon citratus with derived chemicals; Citronellol, Allicin, Nerol and Geraniol respectively. This review could serve as a guide and stimulate researchers toward utilization of African medicinal plants for drugs development against tuberculosis.